BAFF system expression in double negative 2, activated naïve and activated memory B cells in systemic lupus erythematosus - Álvarez Gómez, Jhonatan Antonio; Salazar-Camarena, Diana Celeste; Román-Fernández, Ilce Valeria; Ortiz-Lazareno, Pablo César; Cruz, Alvaro; Muñoz-Valle, José Francisco; Marín-Rosales, Miguel; Espinoza-García, Noemí; Sagrero-Fabela, Nefertari; Palafox-Sánchez, Claudia Azucena (Frontiers in Immunology, 2023)
B cell activating factor (BAFF) has an important role in normal B cell development. The aberrant expression of BAFF is related with the autoimmune diseases development like Systemic Lupus Erythematosus (SLE) for promoting self-reactive B cells survival. BAFF functions are exerted through its receptors BAFF-R (BR3), transmembrane activator calcium modulator and cyclophilin ligand interactor (TACI) and B cell maturation antigen (BCMA) that are reported to have differential expression on B cells in SLE. Recently, atypical B cells that express CD11c have been associated with SLE because they are prone to develop into antibody-secreting cells, however the relationship with BAFF remains unclear. This study aims to analyze the BAFF system expression on CXCR5 -CD11c + atypical B cell subsets double negative 2 (DN2), activated naïve (aNAV), switched memory (SWM) and unswitched memory (USM) B cells. Forty-five SLE patients and 15 healthy subjects (HS) were included. Flow cytometry was used to evaluate the expression of the receptors in the B cell subpopulations. Enzyme-linked immunosorbent assay (ELISA) was performed to quantify the soluble levels of BAFF (sBAFF) and IL-21.We found increased frequency of CXCR5 -CD11c + atypical B cell subpopulations DN2, aNAV, SWM and USM B cells in SLE patients compared to HS. SLE patients had increased expression of membrane BAFF (mBAFF) and BCMA receptor in classic B cell subsets (DN, NAV, SWM and USM). Also, the CXCR5 + CD11c -DN1, resting naïve (rNAV), SWM and USM B cell subsets showed higher mBAFF expression in SLE. CXCR5 -CD11c + atypical B cell subpopulations DN2, SWM and USM B cells showed strong correlations with the expression of BAFF receptors. The atypical B cells DN2 in SLE showed significant decreased expression of TACI, which correlated with higher IL-21 levels. Also, lower expression of TACI in atypical B cell DN2 was associated with high disease activity. These results suggest a participation of the BAFF system in CXCR5 -CD11c + atypical B cell subsets in SLE patients.Decreased TACI expression on atypical B cells DN2 correlated with high disease activity in SLE patients supporting the immunoregulatory role of TACI in autoimmunity.